Renal outcome in children with pelviureteric junction obstruction (PUJO) : a tertiary centre experience - Rahman, Nur Atiqah Abdul (2020)
Background: Antenatal hydronephrosis is a common findings during antenatal scan and pelvi-ureteric junction obstruction is the commonest cause. Dynamic study using radio-isotope scan has become the standard investigation for diagnostic purpose. We reviewed the outcome of children who underwent DTPA/MAG3 scan for suspected PUJO including their clinical presentation, indication for surgery, underlying causes and post-surgical outcome. Methodology: This was a retrospective study looking at clinical data from 2008 until 2018 whom underwent DTPA/MAG3 imaging in a tertiary hospital. Baseline characteristic of the patient, age at the time of diagnosis, indication for undergoing radionuclide scan, type of surgery performed, and post-surgical follow-up investigations were recorded. Result: A total patients of 151 were recruited into the study. Majority were males 101 (66.9%); and 50 of them were females (33.1%). Median age of the patient was four-year- old when the diagnosis was made. Antenatal hydronephrosis and abdominal pain were the commonest clinical presentation warranted for radionuclide scan to be performed. PUJO was confirm in 57 patients (37.7%) of which majority were found on the unilateral side involving left kidney 31 patients (53.1%). Pyeloplasty was performed as corrective surgery in seventy percent of them. Nevertheless, 7 patients (21%) showed persistent obstruction during follow up imaging after the surgery. Conclusion: This study highlighted the importance of follow-up investigation in all antenatal hydronephrosis. Radionuclide scan is the diagnostic tool for PUJO and preferably should be arranged earlier to avoid delay in diagnosis and improve the renal outcome. Potential residual hydronephrosis and obstruction may occur despite corrective pyeloplasty, hence the need for complement imaging as an imperative measure to prevent future risk of chronic kidney disease.